Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 1 - Functions and Limits - 1.3 New Functions from Old Functions - 1.3 Exercises: 42

Answer

$(f\circ g\circ h) (x)=\displaystyle \tan(\frac{\sqrt[3]{x}}{\sqrt[3]{x}-1})$

Work Step by Step

$(f\circ g\circ h) (x)=f[g(h(x))]$ $g(h(x))=g(\displaystyle \sqrt[3]{x})=\frac{\sqrt[3]{x}}{\sqrt[3]{x}-1}$ $f[g(h(x))]=f(\displaystyle \frac{\sqrt[3]{x}}{\sqrt[3]{x}-1})=\tan(\frac{\sqrt[3]{x}}{\sqrt[3]{x}-1})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.